Nghiên cứu lựa chọn phụ gia chống oxi hóa cho mỡ bôi trơn phân hủy sinh học gốc dầu thực vật - Thúy Hà, Nguyễn Thị; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2014)
The use of vegetable oil triglycerides as base oil in biodegradable lubricating grease has been limited due to their susceptibility to oxidative degradation. With the growing concern in seeking environmental safety lubricating grease, shortcomings of vegetable oils in oxidation stability were resolved by adding effective antioxidants. The paper presents the results of research for antioxidant effects on vegetable oil based lubricating greases. Three antioxidants such as alkyl phenol, alkyl diphenylamine and ZDDP were chosen to study. Their individual and synergism effects on grease were well discussed. The ability of improving oxidation stability of vegetable oil based grease was decreased as follows: diphenylamine > dialkyldithiophosphate zinc (ZDDP) > alkyl phenol. The package of diphenylamine and ZDDP with the ratio 1:1 respectively was indicated to be most effective for the grease composition because of their synergism action. Vegetable oil based APP PHSH  with 3 percents of mixture ZDDP/diphenylamine with the ratio 1/1 has the decrease of oxygen pressure by ASTM D 942 less than this one of mineral grease PLC L3 (6 Psi against 20 psi respectively)